Analyzing effects on anterior open bite in twins by PLS-SEM and sobel test - Birant, Sinem; Veznikli, Mert; Kasimoglu, Yelda; Koruyucu, Mine; Evren, Atif Ahmet; Seymen, Figen (SPRINGER HEIDELBERG, 2024)
ObjectiveThis study aimed to assess the different pathways between predictor factors such as zygosity, atypical swallowing, mouth breathing, breastfeeding and bottle feeding related to anterior open bite (AOB) in twins.MethodsThe study was conducted in monozygotic (MZ) and dizygotic (DZ) twin children aged 3-15 years. AOB, atypical swallowing, mouth breathing, feeding type, duration of bottle use, and mouth opening status during sleep were recorded during oral examination. Partial least squares structural equation model (PLS-SEM) and sobel tests were performed to assess the total and indirect effects among the variables on AOB.ResultsA total of 404 children (29.2% MZ;70.8% DZ) participated in this study. The effect of zygosity on mouth breathing in the PLS-SEM model was statistically significant. Conversely, it was determined that mouth breathing effected that atypical swallowing (p = 0.001). Atypical swallowing triggered AOB (p = 0.001). The atypical swallowing has a mediation effect between AOB and mouth breathing (p = 0.020). Mouth breathing causes atypical swallowing and therefore indirectly increases the likelihood of AOB. While breastfeeding decreases AOB incidence (p = 0.023), bottle feeding increases AOB incidence (p = 0.046). The sobel tests show that the fully mediator variable feature of mouth breathing is statistically significant in the negative relation between zygosity and atypical swallowing.ConclusionThe PLS-SEM model showed that mouth breathing triggers atypical swallowing and atypical swallowing triggers AOB. As a result of this chain of relationships, an indirect effect of zygosity on AOB was observed. According to sobel tests, zygosity has an indirect effect on atypical swallowing through mouth breathing, while mouth breathing has a positive indirect effect on AOB through atypical swallowing.Clinical relevanceThis study identified the relationships between different factors and the presence of AOB. The findings of this study demonstrate in detail the relationships between AOB and zygosity, atypical swallowing, mouth breathing, breastfeeding and bottle feeding. Brestfeeding has a reducing effect on the frequency of AOB. Among the nutritional forms, breastfeeding ensures the proper development of the stomatognathic system by working the oro-facial muscles.
Keywords: Pediatric dentistry; Swallowing; Structural equation modeling; Clinical studies/Trials; Orthodontic(s); NONNUTRITIVE SUCKING HABITS; BRAZILIAN CHILDREN; MALOCCLUSIONS; PREVALENCE; MORPHOLOGY; Dentistry, Oral Surgery & Medicine